设\(w = f(x + y + z,xyz)\),其中\(f\)有连续偏导数,则\( { { {\partial}w} \over {\partial {x}}} =\) A: \({f'_1} + yz{f'_2}\) B: \(x{f'_1} + yz{f'_2}\) C: \(yz{f'_1} +x{f'_2}\) D: \({f'_1} +{f'_2}\)
设\(w = f(x + y + z,xyz)\),其中\(f\)有连续偏导数,则\( { { {\partial}w} \over {\partial {x}}} =\) A: \({f'_1} + yz{f'_2}\) B: \(x{f'_1} + yz{f'_2}\) C: \(yz{f'_1} +x{f'_2}\) D: \({f'_1} +{f'_2}\)
由方程\({z^3} - 3xyz = {a^3}\)所确定的隐函数\(z= f(x,y)\)的偏导数\( { { \partial z} \over {\partial x}} = \) A: \( { { yz} \over { { z^2} - xy}}\) B: \(- { { yz} \over { { z^2} - xy}}\) C: \( { { yz} \over { { z^2} +xy}}\) D: \(- { { yz} \over { { z^2}+xy}}\)
由方程\({z^3} - 3xyz = {a^3}\)所确定的隐函数\(z= f(x,y)\)的偏导数\( { { \partial z} \over {\partial x}} = \) A: \( { { yz} \over { { z^2} - xy}}\) B: \(- { { yz} \over { { z^2} - xy}}\) C: \( { { yz} \over { { z^2} +xy}}\) D: \(- { { yz} \over { { z^2}+xy}}\)
已知:()x()-()y()=()1(),()z()-()y()=()2(),则()xy()+()yz()+()zx()-()x()2()-()y()2()-()z()2()的值是
已知:()x()-()y()=()1(),()z()-()y()=()2(),则()xy()+()yz()+()zx()-()x()2()-()y()2()-()z()2()的值是
函数\(y = {x^{ - 4}}{\rm{ + }}2{x^3} - 2x\)的导数为( ). A: \(4{x^3} + 6{x^2} - 2\) B: \( - 4{x^{ - 5}} + 6{x^2} - 2\) C: \( - 4{x^{ - 3}} + 6{x^2} - 2\) D: \( - 4{x^3} + 6{x^2} - 2\)
函数\(y = {x^{ - 4}}{\rm{ + }}2{x^3} - 2x\)的导数为( ). A: \(4{x^3} + 6{x^2} - 2\) B: \( - 4{x^{ - 5}} + 6{x^2} - 2\) C: \( - 4{x^{ - 3}} + 6{x^2} - 2\) D: \( - 4{x^3} + 6{x^2} - 2\)
在x值处于-2~2、4~8时值为“真”,否则为“假”的表达式是______。 A: (2>x>-2)||(4>x>8) B: !(((x<-2)||(x>2))&&((x<=4)||(x>8))) C: (x<2)&&(x>=-2)&&(x>4)&&(x<8) D: (x>-2)&&(x>4)||(x<8)&&(x<2)
在x值处于-2~2、4~8时值为“真”,否则为“假”的表达式是______。 A: (2>x>-2)||(4>x>8) B: !(((x<-2)||(x>2))&&((x<=4)||(x>8))) C: (x<2)&&(x>=-2)&&(x>4)&&(x<8) D: (x>-2)&&(x>4)||(x<8)&&(x<2)
求不定积分[img=112x35]17da6538063a9e4.png[/img]; ( ) A: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/ B: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4))/8 C: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4)) D: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/8
求不定积分[img=112x35]17da6538063a9e4.png[/img]; ( ) A: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/ B: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4))/8 C: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4)) D: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/8
设\(f\left( {x,y,z} \right) = x{y^2} + y{z^2} + z{x^2}\),则\({f_{yz}}\left( {0,-1,0} \right) = \)( ) A: 1 B: 0 C: -1 D: 2
设\(f\left( {x,y,z} \right) = x{y^2} + y{z^2} + z{x^2}\),则\({f_{yz}}\left( {0,-1,0} \right) = \)( ) A: 1 B: 0 C: -1 D: 2
求不定积分[img=121x54]17da653839aa6ae.png[/img]; ( ) A: log(x^2 + 3*x + 25/4)/4 + (5*atan(x/2 + 3/4))/4 B: log(x^2 + 3*x + 25/4)/4 C: (5*atan(x/2 + 3/4))/4 D: log(x^2 + 3*x + 25/4)/4 - (5*atan(x/2 + 3/4))/4
求不定积分[img=121x54]17da653839aa6ae.png[/img]; ( ) A: log(x^2 + 3*x + 25/4)/4 + (5*atan(x/2 + 3/4))/4 B: log(x^2 + 3*x + 25/4)/4 C: (5*atan(x/2 + 3/4))/4 D: log(x^2 + 3*x + 25/4)/4 - (5*atan(x/2 + 3/4))/4
求不定积分[img=132x48]17da6537fc8dad6.png[/img]; ( ) A: -(4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) B: (4*(sin(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) C: (4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) D: (4*(cos(x/2)/2 + 2*cos(x/2)))/(17*exp(2*x))
求不定积分[img=132x48]17da6537fc8dad6.png[/img]; ( ) A: -(4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) B: (4*(sin(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) C: (4*(cos(x/2)/2 + 2*sin(x/2)))/(17*exp(2*x)) D: (4*(cos(x/2)/2 + 2*cos(x/2)))/(17*exp(2*x))
求函数[img=173x42]17da65390bf2806.png[/img]的导数; ( ) A: tan(pi/4 + x/2) B: (tan(pi/4 + x/2)^2/2 ) /tan(pi/4 ) C: (tan(pi/4 + x/2)^2/2 + 1/2) D: (tan(pi/4 + x/2)^2/2 + 1/2) /tan(pi/4 + x/2)
求函数[img=173x42]17da65390bf2806.png[/img]的导数; ( ) A: tan(pi/4 + x/2) B: (tan(pi/4 + x/2)^2/2 ) /tan(pi/4 ) C: (tan(pi/4 + x/2)^2/2 + 1/2) D: (tan(pi/4 + x/2)^2/2 + 1/2) /tan(pi/4 + x/2)